Workplace interpersonal relationships and turnover intentions among care workers working in older adult care facilities in Japan: a mediation analysis comparing direct and mediated effects via psychological distress - Shinya Takeda; Toshiki Fukuzaki (BMC Nursing, 2024)
Abstract Background This study aimed to investigate the relationship between workplace interpersonal relationships, psychological distress, and turnover intentions among care workers working in older adult care facilities. Methods An anonymous online survey among 811 care workers in Tottori Prefecture, Japan, was conducted between November and December 2023. The data were collected using the Workplace Interpersonal Problems Scale for care workers (WIPS), the K6 scale to assess psychological distress, the Turnover Intention Scale and basic attributes. Responses were obtained from 254 participants with a response rate of 31.3%. The low response rate suggests that selection bias may have affected the results of this study. Results The results of the mediation analysis for the WIPS subscale which was adjusted for basic attributes show that the direct effects of insufficient communication and a sense of unfair workload were stronger than the mediating effects of psychological distress (Insufficient communication: direct effect: β = 0.319 [95% CI = 0.192, 0.459]; mediation effect: β = 0.194 [95% CI = 0.105, 0.285]), sense of unfair workload: direct effect: β = 0.314 [95% CI = 0.187, 0.443]; mediation effect: β = 0.190 [95% CI = 0.113, 0.268]). In these other four WIPS subscales, psychological distress was partially mediated (bullying: direct effect: β = 0.207 [95% CI = 0.091, 0.322]; mediation effect: β = 0.204 [95% CI = 0.135, 0.290], different attitudes to care work: direct effect: β = 0.278 [95% CI = 0.140, 0.401]; mediation effect: β = 0.204 [95% CI = 0.128, 0.293], difficulty in guidance for subordinates/new staff: direct effect: β = 0.207 [95% CI = 0.072, 0.329]; mediation effect: β = 0.219[95% CI = 0.141, 0.313], labeling: direct effect: β = 0.198 [95% CI = 0.073, 0.330]; mediation effect: β = 0.211 [95% CI = 0.143, 0.287]). Conclusions This study revealed that some workplace interpersonal problems have a stronger direct effect on turnover intentions, whereas others have a stronger mediating effect on turnover intentions through psychological distress. Workplace interpersonal problems are predictors of turnover intentions among care workers working in elderly care facilities, and different workplace interpersonal problems may be targeted for intervention to reduce turnover intentions.